ANALISIS PENERAPAN STANDAR OPERASIONAL PROSEDUR PELAYANAN PUBLIK PEMBUATAN PASPOR (STUDI PADA KANTOR IMIGRASI KELAS I TPI KENDARI) - Rospianti, Ayu; Kadir, Abdul; BB, Suryani (REZ PUBLICA, 2019)
The standard operating procedure is a system compiled work process designed systematically to accomplish the planned organizationâ€™s purposes. In the standard operating organization, procedures are the most important capital for the organization to control the entire decision and his activity in a systematic and efficient corridor.The purpose of this study is to know how operational standards are operational in the public service in this process passport making, this study is done in the immigration office class I TPI kendari in November 2018. The kind of research used is a qualitative description of a research subject: An Immigration Office Clerk, Passport Workes, and the People/Applicant who are engaged in the making of passport by using data collection techniques through observation, interviews, documentation.Based on the results of the research, it has been suggested that with a standard operating procedure this procedure has a primary purpose to process the performance of the work is done with neat, orderly and systematic for, beginning to end, as a working guide so that the activities within the company can be controlled, so that a target that wants to be reached can be achieved maximum, in the immigration office class I TPI Kendari to be a reference to developing the quality of the work to be better.Â